The age of the dream palace : cinema and society in 1930s Britain - Richards, Jeffrey (Cinema and society., 2010)
The period between the two world wars is often named 'the golden age of the cinema' in Britain. This definitive and entertaining book on the cinema and cinema-goers of the era is herewith reissued with a new Introduction. Jeffrey Richards, described by Philip French as 'a shrewd critic, a compulsive moviegoer, and a professional historian', tells the absorbing story of the cinema during the decade that produced Alfred Hitchcock's thrillers, the musicals of Jessie Matthews and Alexander Korda's epics. He examines the role of going to the pictures in people's lives during a tough period when, in.